Integrating intercultural activities into teaching Mandarin for international students in China - Liu, Na (Frontiers in Psychology, 2022)
This study explores the intercultural activities in teaching Mandarin to international students in China. Data were collected through class observations and semi-structured interviews and analyzed through thematic analysis using the framework of Byram’s notion of intercultural competence in language teaching and learning. The results show that intercultural activities can effectively promote Mandarin teaching for international students. The findings also suggest Mandarin teachers can provide more opportunities for international students to share their values and opinions and adopt more activities to teach cultural knowledge. Accordingly, recommendations on preparing intercultural competence are concluded and put forward, which might support future teaching.